COMMUNITY SERVICE EDUCATION ON PHYSIOLOGICAL-PSYCHOLOGICAL CHANGES IN WIVES AND EARLY DETECTION OF PREGNANCY BASED ON BATAK CULTURE IN MEDAN TUNTUNGAN DISTRICT - Leni Agustina; Noer Desmie; Cahya Aisyah Daulay (Cattleya Darmaya Fortuna, 2025)
Pregnancy is a crucial period that is accompanied by significant physiological and psychological changes in the mother. The lack of understanding of these normal changes, as well as the lack of early detection of pregnancy risks, is often exacerbated by the influence of myths or inappropriate traditions in society. This community service activity aims to increase the knowledge of pregnant women and families in dealing with changes during pregnancy and increase awareness of the importance of early detection of pregnancy risks through the approach of local wisdom of Batak Culture. The program will be held on October 21, 2024 with interactive counseling methods, early detection demonstrations, and group discussions. The results of the evaluation showed a significant increase in participants' understanding of the management of physiological-psychological changes and awareness of pregnancy warning signs. Culture-based approaches have proven to be effective in minimizing communication barriers, so that people are more open and proactive in utilizing medical health services according to standards.